Local Wisdom of Settlement Growth in theUrban Fringe Areas - Bambang Setioko (RUAS (Review of Urbanism and Architectural Studies), 2011)
The population growth in the urban fringe area of developed countries is dominated by the urban sprawl and followed by “white flight phenomena”. In Indonesia, although the physically growth of settlements is similar, but the socially one is different. The modern housing estates have been built in the next to the rural settlements. In addition, the autonomous settlements have been emerged surrounding housing estates; the spread settlements will integrate in the following years. This research has been done with the qualitative methods and successfully revealing the existence of local wisdomof settlement growth in Semarang fringe area.Keywords: fringe area, urban sprawl, white flight, local wisdom